Grow for flavor - Wong, James, 1981- (Firefly Books, 2016)
Gardeners can be disappointed by the insipid flavor of the vegetables and fruit that they have so carefully nurtured. The problem, according to botanist James Wong, is that many conventional gardening practices are based on pure myth or faulty science. They create bumper crops at the expense of flavor and nutrition. It doesn't have to be that way. After trial and error of cutting-edge horticultural techniques and extensive review of more than 2,000 journal papers from around the globe, Wong turns the tables on old-school advice with a radical new system that transforms the flavor and nutrition of homegrown produce.